A Theology Of Reading : the Hermeneutics Of Love - Jacobs, Alan (Routledge, 2018)
If the whole of the Christian life is to be governed by the?law of love"?the twofold love of God and one's neighbor?what might it mean to read lovingly? That is the question that drives this unique book. Through theological reflection interspersed with readings of literary texts (Shakespeare and Cervantes, Nabokov and Nicholson Baker, George Eliot and W.H. Auden and Dickens), Jacobs pursues an elusive quarry: the charitable reader.